Leadership by customers? New roles of service companies' customers - Peter Maas; Albert Graf (Zeitschrift für Personalforschung (ZfP), 2004)
In this paper we bring together two worlds that are usually strictly separated in research: leadership and customers. Until now leadership research has concentrated particularly on internal organizational processes, whereas customers were analyzed preferably in the context of marketing and service management. Research shows that the range of roles and functions of customers as key company stakeholders has changed dramatically in the last few years. Especially in service companies, customers (and communities), thought of as prosumers (producers and consumers), are active players, which can exert significant influence particularly on customer contact employees and on employee leadership. As only few of the established leadership concepts are open to an inclusion of customers, we choose Kerr/Jermier's (1978) substitute for leadership theory to show how the relationship between boundary spanning employees and customers can be linked to the relationship between an employee (as a follower) and his supervisor (as a leader).The analysis of this interrelatedness shows that customers can actually assume some leadership functions which subsequently will not only affect the behavior of the employees but also that of leaders. If leadership research wants to take up this challenge, it has to rethink its concepts to include new context factors relevant to the organisation. Corresponding implications and future directions for leadership research and practice are outlined.
Keywords: 650; Substitutes for Leadership; Leadership by Customers; Customer Involvement; Service Management